If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-2x + 3) + 4x + -5 = -50 Reorder the terms: 5(3 + -2x) + 4x + -5 = -50 (3 * 5 + -2x * 5) + 4x + -5 = -50 (15 + -10x) + 4x + -5 = -50 Reorder the terms: 15 + -5 + -10x + 4x = -50 Combine like terms: 15 + -5 = 10 10 + -10x + 4x = -50 Combine like terms: -10x + 4x = -6x 10 + -6x = -50 Solving 10 + -6x = -50 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -6x = -50 + -10 Combine like terms: 10 + -10 = 0 0 + -6x = -50 + -10 -6x = -50 + -10 Combine like terms: -50 + -10 = -60 -6x = -60 Divide each side by '-6'. x = 10 Simplifying x = 10
| 4(-4x+3)-2x+1=85 | | 2x^2+28x+98=24 | | 12x-2(8+5x)=12-11x | | 168=106-w | | x^2-3x=6x | | 4s^2=8s+9 | | xy-3x=-4 | | -m^2+3m-3=2 | | (3x^4)(2x^7)= | | 8x^2-27x-20= | | 4(y+2)-5y=y+12 | | (7^-1z^-3x)(5z^3x^4)^-2/4z^-3x^-3)^2 | | 3y^2-17xy-6x^2= | | -4a^2+3a-5=2 | | y=25x+30y | | 5(5.3)+y=2 | | 7x+27=64 | | x+7y=-122 | | 3(2-1x)+1=-4(1x+1) | | 3(2-1x)+1=-4(1x+4) | | y=x^2+20x+106 | | -23-8y=52 | | 9x-5x-(2+6x)+8=6x-(5x+2+3x)+2 | | (2x-5y)2= | | -3v-5v-3=-5 | | (1-3n)/4=2n-3(x-1/2) | | -k^2-2k-1=0 | | 11x+16y=10 | | Sqrt(8x-15)=sqrt(6x-3) | | Sqrt(8x-15)=sqrt(6u-3) | | -2b^2-8b-8=0 | | m-8=x |